A kind of anti-fading carbon composite modified negative electrode material for power battery and preparation method thereof

By reacting tetraethyl titanate with water in the carbon composite modified negative electrode material to form conductive titanium dioxide, and reacting with polyvinyl phosphonic acid to form conductive modified polyvinyl phosphonic acid, the problems of insufficient conductivity and poor circulation performance in the prior art are solved, and efficient battery circulation and conductivity improvement are achieved.

CN119306226BActive Publication Date: 2025-05-02湖南镕锂新材料科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411861801.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-05-02
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing carbon composite modified negative electrode materials have problems such as insufficient conductivity and poor circulation performance in high-energy-density battery applications, especially the absence of adhesion between silicon carbon particles and the inability to form a good conductive network.

Method used

Tetraethyl titanate is used to react with water to form titanium dioxide with hydroxyl groups on the surface, and react with polyvinyl phosphonic acid to form conductively modified polyvinyl phosphonic acid. The modified polyvinylphosphonic acid is mixed with mesoporous silica, and through ultrasonic dispersion and vapor deposition technology, a carbon composite modified negative electrode material with electrical conductivity and good bonding strength is formed.

Benefits of technology

The cycling performance and conductivity of the battery are significantly improved, the collapse of the electrode structure and the fall off of the material are avoided, and the mechanical properties of the carbon material are enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides an anti-fading carbon composite modified negative electrode material for a power battery and a preparation method thereof, and belongs to the technical field of electrode materials for new energy batteries. The preparation method comprises: adding tetraethyl titanate and water to ethanol, stirring the reaction, and collecting a white precipitate product A; adding product A and polyvinylphosphonic acid to toluene, heating under nitrogen protection for reaction, cooling to room temperature, and collecting a solid product B; adding product B to a cyclohexane solvent to form a suspension, adding n-butyl lithium solution to the suspension under stirring conditions for reaction, and collecting a solid product C; adding product C and a silicon source to ethanol, stirring the reaction after ultrasonic dispersion, and collecting a solid product D; placing product D in a chemical vapor deposition reactor, selecting acetylene gas as a carbon source, and performing vapor phase precipitation to obtain a carbon composite modified negative electrode material. The carbon composite modified negative electrode material obtained by the above method can inhibit the volume expansion of silicon and has anti-fading performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy battery electrode materials, and in particular to an anti-fading carbon composite modified negative electrode material for a power battery and a preparation method thereof. Background Art

[0002] Carbon-based negative electrode materials are widely used in secondary batteries due to their high electronic conductivity, good cycle performance and abundant resources. Among them, graphite negative electrode materials are the most widely used in commercial applications, but their theoretical capacity is only 372mAh / g and their rate capacity characteristics are poor, which limits their application in high energy density batteries. Therefore, carbon composite modified negative electrode materials have been derived.

[0003] At present, carbon composite modified negative electrode materials mainly include silicon-carbon composite materials, silicon / graphite / carbon composite materials, carbon foam composite materials and MXene-based composite materials. Among them, the conventional silicon modification method of silicon-carbon composite materials is to form a carbon buffer layer on the surface of silicon material. Its structure: on the one hand, due to the high theoretical specific capacity of silicon material, it can improve the capacity of the battery to make up for the deficiency of carbon material; on the other hand, the carbon buffer layer can suppress the defect of volume expansion of silicon material during charging and discharging. However, it can be found in actual use that simply coating the surface of silicon material with a carbon buffer layer is not very ideal for improvement. Since silicon-carbon particles do not adhere to each other and cannot form a good conductive network, the conductivity needs to be improved. Summary of the invention

[0004] In order to solve the problems mentioned in the background technology, the present invention provides a method for preparing an anti-degradation carbon composite modified negative electrode material for a power battery. The method takes a silicon source as the core and adopts a special adhesive system to coat a carbon layer on the surface of the silicon source, so that the adhesion of silicon-carbon particles is improved, and the adhesive system is conductive, thereby improving the conductivity.

[0005] Specifically:

[0006] A method for preparing an anti-fading carbon composite modified negative electrode material for a power battery, the steps comprising:

[0007] Step 1: adding tetraethyl titanate and water into ethanol, stirring for reaction, collecting the white precipitate product A after the reaction is completed, washing, and vacuum drying for later use;

[0008] Step 2: Add the product A of step 1 and polyvinylphosphonic acid to toluene, stir evenly, heat to 100-120° C. under nitrogen protection for reaction, cool to room temperature after the reaction, collect the solid product B, wash, and vacuum dry for later use;

[0009] Step 3, adding the product B of step 2 into cyclohexane solvent to form a suspension, adding n-butyl lithium solution dropwise to the suspension under argon protection, reaction temperature -5 to 0°C, stirring, continuing the reaction after the addition is completed, heating to room temperature after the reaction is completed, collecting the solid product C, washing, vacuum drying, and setting aside;

[0010] Step 4: Add the product C of step 3 and the silicon source into ethanol, stir and react after ultrasonic dispersion, collect the solid product D after the reaction, vacuum dry it and set aside;

[0011] Step 5: Place the product D of step 4 into a chemical vapor deposition reactor, select acetylene gas as the carbon source, and perform vapor deposition to obtain a carbon composite modified negative electrode material.

[0012] Furthermore, in step 1, the mass ratio of tetraethyl titanate to water is 1:0.4-0.6, and the volume ratio of ethanol to tetraethyl titanate is 8-12:1.

[0013] Furthermore, in step 1, the stirring speed is 300-500 rpm; the reaction time is 3-5 hours; anhydrous ethanol is used for washing; and the vacuum drying temperature is 60-80°C.

[0014] Furthermore, in step 2, the mass ratio of product A, polyvinylphosphonic acid and toluene is 1:0.8-1.2:7.2-8.8.

[0015] Furthermore, in step 2, the reaction time is 8 to 12 hours; toluene is used for washing; and the vacuum drying temperature is 60 to 80°C.

[0016] Furthermore, in step three, the mass ratio of product B to cyclohexane is 1:10-11; the mass fraction of n-butyl lithium in the n-butyl lithium solution is 15%-20%, cyclohexane is selected as the solvent, and the mass ratio of n-butyl lithium to product B is 0.2-0.3:1.

[0017] Furthermore, in step 3, the stirring speed is 200-300 rpm; the dropping speed of the n-butyl lithium solution is controlled at 0.5-2 mL / min; the reaction time is 4-6 h; anhydrous ethanol is used for washing; and the vacuum drying temperature is 40-60° C.

[0018] Furthermore, in step 4, the silicon source is mesoporous silica powder; the mass ratio of product C to silicon source is 1-3:1; ultrasound is applied for 30-60 minutes at a power of 200-300 W to fully disperse the two in the solution to avoid agglomeration; the stirring speed is 300-500 rpm; the reaction time is 2-4 hours; and the vacuum drying temperature is 60-80°C.

[0019] Furthermore, in step 5, the vapor deposition reaction temperature is 600-800° C., the reaction pressure is 1-5 kPa, and the lower pressure is conducive to the adsorption and diffusion of the carbon source gas on the solid surface. Acetylene gas is introduced at a flow rate of 20-40 mL / min, and the reaction time is 2-4 h.

[0020] The present invention also provides an anti-fading carbon composite modified negative electrode material for a power battery, which is prepared by the above-mentioned preparation method.

[0021] Compared with the prior art, the present invention has the following beneficial features:

[0022] 1. The present invention obtains titanium dioxide with hydroxyl groups on the surface by reacting tetraethyl titanate with water. The hydroxyl groups on the titanium dioxide can be bonded with the phosphonic acid groups of polyvinylphosphonic acid. The titanium dioxide has conductivity, so that the modified polyvinylphosphonic acid has conductive properties. In addition, the polyvinylphosphonic acid can improve the dispersibility of titanium dioxide, prevent its agglomeration, and make the electron conduction channel more unobstructed. The two complement each other. Subsequently, the modified polyvinylphosphonic acid is mixed with n-butyl lithium, and the lithium-containing modified polyvinylphosphonic acid is obtained through the reaction of the two. The specially modified polyvinylphosphonic acid is mixed with a mesoporous silica solution, and the polyvinylphosphonic acid can be fully dispersed in the gaps and surface of the silica, and the polyvinylphosphonic acid is well bonded to the silica, so that the surface and the interior of the mesoporous silica have conductivity. In addition, by pre-embedding lithium, the volume expansion of the electrode occurs in advance, which avoids the collapse of the electrode structure and the shedding of the electrode material during the subsequent cycle charge and discharge of the battery, which helps to significantly improve the cycle performance of the battery.

[0023] 2. The present invention coats specially modified polyvinylphosphonic acid on the surface of mesoporous silica. The carbon source generated by vapor precipitation has good adhesion to the coating layer, and the presence of titanium dioxide on the polyvinylphosphonic acid promotes the adsorption, dissociation and diffusion of the carbon source gas. The titanium atoms can be embedded in the lattice structure of the carbon material, changing the electronic structure and conductivity of the carbon material. At the same time, this doping can enhance the mechanical properties of the carbon material, such as improving the strength and toughness of the carbon nanotubes. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] In order to facilitate those skilled in the art to implement the present invention, some of the reagents used in the embodiments and comparative examples are now described:

[0026] Tetraethyl titanate: Wuhan Lanabai;

[0027] Ethanol: anhydrous ethanol, Shanghai Kelong Chemical;

[0028] Polyvinylphosphonic acid: Shanghai MacLean Biochemical Technology;

[0029] Toluene: Shanghai Xiangheyi Chemical Technology;

[0030] Cyclohexane: Shandong Hengshuo Chemical Co., Ltd.;

[0031] n-Butyl lithium: Shaoxing Hualun Chemical;

[0032] Silicon source: mesoporous silica, particle size ≤ 20um, pore size ≥ 200nm, Hangzhou Jikang New Materials;

[0033] Acetylene: Guangzhou Yuejia Gas;

[0034] Carboxymethyl cellulose: Shandong Chengxin Chemical.

[0035] Example 1

[0036] A carbon composite modified negative electrode material for a power battery with an anti-fading property, and a preparation method thereof comprising:

[0037] Step 1, adding tetraethyl titanate and water in a mass ratio of 1:0.4 to ethanol, the volume ratio of ethanol to tetraethyl titanate is 8:1, stirring and reacting at room temperature, the stirring speed is 300 rpm, the reaction time is 3 hours, and after the reaction is completed, the white precipitate product A is collected, washed with anhydrous ethanol, and vacuum dried at 60°C for 12 hours for standby use;

[0038] Step 2: Add the product A of step 1 and polyvinylphosphonic acid to toluene, the mass ratio of product A, polyvinylphosphonic acid and toluene is 1:0.8:7.2, stir evenly, heat to 100°C under nitrogen protection for reaction, the reaction time is 8h, cool to room temperature after the reaction is completed, collect the solid product B, wash with toluene, and vacuum dry at 60°C for 12h for standby use;

[0039] Step 3, adding the product B of step 2 to a cyclohexane solvent, the mass ratio of B to cyclohexane is 1:10, to form a suspension, under argon protection, lowering the temperature to -5°C, adding n-butyl lithium solution to the suspension under stirring conditions at this temperature, the stirring speed is 200rpm, the dropping speed of the n-butyl lithium solution can be controlled at 0.5mL / min, and continuing the reaction after the dropwise addition is completed, the reaction time is 4h, the temperature is raised to room temperature after the reaction is completed, the solid product C is collected, washed with anhydrous ethanol, and vacuum dried at 40°C for 12h for standby use; the mass fraction of n-butyl lithium in the n-butyl lithium solution is 15%, cyclohexane is selected as the solvent, and the mass ratio of n-butyl lithium to product B is 0.2:1;

[0040] Step 4: Add the product C of step 3 and a silicon source to ethanol, wherein the mass ratio of the silicon source, the product C, and the ethanol is 1:1:20, and stir to react after ultrasonic dispersion, ultrasonic for 30 minutes, the ultrasonic power is 200 W, the stirring speed is 300 rpm, and the reaction time is 2 hours. After the reaction is completed, collect the solid product D, vacuum dry it at 60°C for 12 hours, and set aside;

[0041] Step 5. Place the product D of step 4 into a chemical vapor deposition reactor. Before the reaction, introduce argon (Ar) as a protective gas with a flow rate of 50 mL / min for 5 minutes to exclude the air in the reactor. Select acetylene gas as the carbon source. The acetylene gas is introduced into the chemical vapor deposition reactor at a flow rate of 20 mL / min. The temperature is raised to 600°C and the reaction pressure is 1 kPa. Gas phase precipitation is carried out for a reaction time of 2 hours. After the reaction is completed, stop introducing acetylene gas first, and then naturally cool the reactor to room temperature under the protection of argon to prevent the generated carbon coating from reacting with oxygen in the air at high temperature and being destroyed. Take out the product to obtain the product.

[0042] Example 2

[0043] A carbon composite modified negative electrode material for a power battery with an anti-fading property, and a preparation method thereof comprising:

[0044] Step 1, adding tetraethyl titanate and water to ethanol in a mass ratio of 1:0.6, the volume ratio of ethanol to tetraethyl titanate is 12:1, stirring and reacting at room temperature, the stirring speed is 500 rpm, the reaction time is 5 hours, and after the reaction is completed, the white precipitate product A is collected, washed with anhydrous ethanol, and vacuum dried at 80°C for 14 hours for standby use;

[0045] Step 2: Add the product A of step 1 and polyvinylphosphonic acid to toluene, the mass ratio of product A, polyvinylphosphonic acid and toluene is 1:1.2:8.8, stir evenly, heat to 120°C under nitrogen protection for reaction, the reaction time is 12h, cool to room temperature after the reaction is completed, collect the solid product B, wash with toluene, and vacuum dry at 80°C for 14h for standby use;

[0046] Step 3, adding the product B of step 2 to a cyclohexane solvent, the mass ratio of B to cyclohexane is 1:11, to form a suspension, under argon protection, lowering the temperature to 0°C, adding n-butyl lithium solution to the suspension under stirring conditions at this temperature, the stirring speed is 300rpm, the dropping speed of the n-butyl lithium solution can be controlled at 2mL / min, and continuing the reaction after the dropwise addition is completed, the reaction time is 6h, the temperature is raised to room temperature after the reaction is completed, the solid product C is collected, washed with anhydrous ethanol, and vacuum dried at 60°C for 14h for standby use; the mass fraction of n-butyl lithium in the n-butyl lithium solution is 20%, cyclohexane is selected as the solvent, and the mass ratio of n-butyl lithium to product B is 0.3:1;

[0047] Step 4: Add the product C of step 3 and a silicon source to ethanol, wherein the mass ratio of the silicon source, the product C, and the ethanol is 1:3:30, and stir to react after ultrasonic dispersion, ultrasonic for 60 min, the ultrasonic power is 300 W, the stirring speed is 500 rpm, and the reaction time is 4 h. After the reaction is completed, collect the solid product D, vacuum dry it at 80 ° C for 14 h, and set aside;

[0048] Step 5. Place the product D of step 4 into a chemical vapor deposition reactor. Before the reaction, introduce argon (Ar) as a protective gas with a flow rate of 50 mL / min for 5 minutes to exclude the air in the reactor. Select acetylene gas as the carbon source. The acetylene gas is introduced into the chemical vapor deposition reactor at a flow rate of 40 mL / min. The temperature is raised to 800°C and the reaction pressure is 5 kPa. Gas phase precipitation is carried out for a reaction time of 4 hours. After the reaction is completed, stop introducing acetylene gas first, and then naturally cool the reactor to room temperature under the protection of argon to prevent the generated carbon coating from reacting with oxygen in the air at high temperature and being destroyed. Take out the product to obtain the product.

[0049] Example 3

[0050] A carbon composite modified negative electrode material for a power battery with an anti-fading property, and a preparation method thereof comprising:

[0051] Step 1, adding tetraethyl titanate and water to ethanol in a mass ratio of 1:0.6, the volume ratio of ethanol to tetraethyl titanate is 8:1, stirring and reacting at room temperature, the stirring speed is 500 rpm, the reaction time is 3 hours, and after the reaction is completed, the white precipitate product A is collected, washed with anhydrous ethanol, and vacuum dried at 80°C for 12 hours for standby use;

[0052] Step 2: Add the product A of step 1 and polyvinylphosphonic acid to toluene, the mass ratio of product A, polyvinylphosphonic acid and toluene is 1:1:8, stir evenly, heat to 110°C under nitrogen protection for reaction, the reaction time is 10h, cool to room temperature after the reaction is completed, collect the solid product B, wash with toluene, and vacuum dry at 70°C for 13h for standby use;

[0053] Step 3, adding the product B of step 2 to a cyclohexane solvent, the mass ratio of B to cyclohexane is 1:10, to form a suspension, under argon protection, lowering the temperature to -2°C, adding n-butyl lithium solution to the suspension under stirring conditions at this temperature, the stirring speed is 200rpm, the dropping speed of the n-butyl lithium solution can be controlled at 1.2mL / min, continuing the reaction after the addition is completed, the reaction time is 5h, the temperature is raised to room temperature after the reaction is completed, the solid product C is collected, washed with anhydrous ethanol, and vacuum dried at 50°C for 14h for standby use; the mass fraction of n-butyl lithium in the n-butyl lithium solution is 15%, cyclohexane is selected as the solvent, and the mass ratio of n-butyl lithium to product B is 0.2:1;

[0054] Step 4: Add the product C of step 3 and a silicon source to ethanol, wherein the mass ratio of the silicon source, the product C, and the ethanol is 1:2:25, and stir to react after ultrasonic dispersion, ultrasonic for 50 min, the ultrasonic power is 260 W, the stirring speed is 400 rpm, and the reaction time is 3 h. After the reaction is completed, collect the solid product D, vacuum dry it at 70° C. for 13 h, and set aside;

[0055] Step 5. Place the product D of step 4 into a chemical vapor deposition reactor. Before the reaction, introduce argon (Ar) as a protective gas with a flow rate of 50 mL / min for 5 minutes to exclude the air in the reactor. Select acetylene gas as the carbon source. The acetylene gas is introduced into the chemical vapor deposition reactor at a flow rate of 30 mL / min. The temperature is raised to 700°C and the reaction pressure is 3 kPa. Gas phase precipitation is carried out for a reaction time of 3 hours. After the reaction is completed, stop introducing acetylene gas first, and then naturally cool the reactor to room temperature under the protection of argon to prevent the generated carbon coating from reacting with oxygen in the air at high temperature and being destroyed. Take out the product to obtain the product.

[0056] Comparative Example 1

[0057] A carbon composite negative electrode material with a silicon source coated with asphalt, the preparation method of which comprises:

[0058] Step 1, disperse mesoporous silica and carboxymethyl cellulose in an aqueous solution of ethanol, the mass ratio of mesoporous silica to carboxymethyl cellulose is 5:3, adjust the solid content of the slurry to 35%, and obtain a mixed slurry with a viscosity of 1600 cP. Spray granulation is performed on a spray dryer with an inlet temperature of 220°C and an outlet temperature of 130°C at a feed rate of 60 mL / min. Then, the sample after spray granulation is transferred to an atmosphere furnace, and the temperature is increased to 850°C at a nitrogen flow rate of 5 L / min and a heating rate of 5°C / min. Pyrolysis treatment is performed for 3 hours. After naturally cooling to room temperature, the small silicon-carbon particles are obtained through a 200-mesh sieve.

[0059] Step 2: Mix the small silicon-carbon particles and the low-temperature asphalt solid phase evenly and transfer them to a fusion coating machine. The mass ratio of the small silicon-carbon particles to the low-temperature asphalt is 10:3. At a nitrogen flow rate of 5 L / min and a stirring speed of 100 rpm, heat the mixture to 450°C at a heating rate of 2°C / min and keep it warm for 3 hours. After the material cools to room temperature, place it in an atmosphere furnace and heat it to 1050°C at a nitrogen flow rate of 5 L / min and a heating rate of 5°C / min. Sinter it at high temperature for 4 hours. After high-temperature sintering, cool to room temperature, crush it mechanically and pass it through a 200-mesh sieve to obtain the product.

[0060] Comparative Example 2

[0061] A carbon composite modified negative electrode material, the preparation method of which comprises:

[0062] Step 1, adding polyvinylphosphonic acid to cyclohexane solvent, the mass ratio of polyvinylphosphonic acid to cyclohexane is 1:10, forming a suspension, under argon protection, lowering the temperature to -5°C, adding n-butyl lithium solution to the suspension under stirring conditions at this temperature, the stirring speed is 200rpm, the dropping speed of the n-butyl lithium solution can be controlled at 0.5mL / min, continuing the reaction after the dropwise addition is completed, the reaction time is 4h, the temperature is raised to room temperature after the reaction is completed, the solid product E is collected, washed with anhydrous ethanol, and vacuum dried at 40°C for 12h for standby use; the mass fraction of n-butyl lithium in the n-butyl lithium solution is 15%, cyclohexane is selected as the solvent, and the mass ratio of n-butyl lithium to polyvinylphosphonic acid is 0.2:1;

[0063] Step 2: Add the product E of step 1 and a silicon source to ethanol, wherein the mass ratio of the silicon source, the product E, and the ethanol is 1:1:20, and stir to react after ultrasonic dispersion, ultrasonic for 30 minutes, the ultrasonic power is 200 W, the stirring speed is 300 rpm, and the reaction time is 2 hours. After the reaction is completed, collect the solid product F, vacuum dry it at 60°C for 12 hours, and set aside;

[0064] Step 3: Put the product F of step 2 into a chemical vapor deposition reactor. Before the reaction, introduce argon (Ar) as a protective gas, and control the flow rate at 50 mL / min for 5 minutes to exclude the air in the reactor. Select acetylene gas as the carbon source, and introduce acetylene gas at a flow rate of 20 mL / min into the chemical vapor deposition reactor. Raise the temperature to 600°C, the reaction pressure is 1 kPa, and vapor precipitation is carried out for a reaction time of 2 hours. After the reaction is completed, stop introducing acetylene gas, and then naturally cool the reactor to room temperature under the protection of argon to prevent the generated carbon coating from reacting with oxygen in the air at high temperature and being destroyed. Take out the product to obtain the product.

[0065] Battery Test:

[0066] The negative electrode materials obtained from the above examples and comparative examples were used in the battery for experiments. Battery assembly process: The negative electrode material, conductive agent (SP), CMC and SBR were mixed in a mass ratio of 95:1.5:1.5:2, and coated on copper foil to obtain a negative electrode sheet. According to a mass ratio of 96.5:2:1.5, the positive electrode active material lithium cobalt oxide, conductive agent (SP) and PVDF were mixed evenly and coated on aluminum foil to obtain a positive electrode sheet. The electrolyte was 1 mol / L LiPF6+EC+EMC, and the diaphragm was a polyethylene / propylene composite microporous membrane. They were assembled into a battery.

[0067] Test the first discharge capacity at 0.1C, the first charge and discharge efficiency; the capacity retention rate after 50 cycles at a rate of 0.5C; the capacity retention rate after 50 cycles at a rate of 1C; the test results are as follows:

[0068] 0.1C first discharge capacity (mAh / g) First charge and discharge efficiency (%) Capacity retention rate after 50 cycles at 0.5C rate (%) Capacity retention rate after 50 cycles at 1C rate (%) Example 1 884.1 90.3 79.4 68.9 Example 2 869.3 90.5 81.3 70.6 Example 3 881.6 91.6 78.7 70.1 Comparative Example 1 733.9 71.4 62.3 53.9 Comparative Example 2 664.8 65.3 61.7 55.4

[0069] Through the above test results, it can be found that Examples 1-3 of the present invention have high initial charge and discharge capacity, initial efficiency and excellent long cycle capacity retention rate. The values ​​of Comparative Example 1 and Comparative Example 2 are much lower than those of Examples 1-3. It can be seen from this that the anti-fading carbon composite modified negative electrode material of the present invention has high conductivity, high capacity, high rate charge and discharge performance and long cycle performance.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an anti-fading carbon composite modified negative electrode material for a power battery, characterized in that: The steps include: Step 1: adding tetraethyl titanate and water into ethanol, stirring for reaction, collecting the white precipitate product A after the reaction is completed, washing, and vacuum drying for later use; Step 2: Add the product A of step 1 and polyvinylphosphonic acid to toluene, stir evenly, heat to 100-120° C. under nitrogen protection for reaction, cool to room temperature after the reaction, collect the solid product B, wash, and vacuum dry for later use; Step 3, adding the product B of step 2 into cyclohexane solvent to form a suspension, adding n-butyl lithium solution dropwise to the suspension under argon protection, reaction temperature -5 to 0°C, stirring, continuing the reaction after the addition is completed, heating to room temperature after the reaction is completed, collecting the solid product C, washing, vacuum drying, and setting aside; Step 4: Add the product C of step 3 and the silicon source into ethanol, stir and react after ultrasonic dispersion, collect the solid product D after the reaction, vacuum dry it and set aside; Step 5: Place the product D of step 4 into a chemical vapor deposition reactor, select acetylene gas as the carbon source, and perform vapor deposition to obtain a carbon composite modified negative electrode material.

2. The preparation method according to claim 1, characterized in that: In step 1, the mass ratio of tetraethyl titanate to water is 1:0.4-0.6, and the volume ratio of ethanol to tetraethyl titanate is 8-12:

1.

3. The preparation method according to claim 1, characterized in that: In step 1, the stirring speed is 300-500 rpm; the reaction time is 3-5 hours; anhydrous ethanol is used for washing; and the vacuum drying temperature is 60-80°C.

4. The preparation method according to claim 1, characterized in that: In step 2, the mass ratio of product A, polyvinylphosphonic acid and toluene is 1:0.8-1.2:7.2-8.

8.

5. The preparation method according to claim 1, characterized in that: In step 2, the reaction time is 8 to 12 hours; toluene is used for washing; and the vacuum drying temperature is 60 to 80°C.

6. The preparation method according to claim 1, characterized in that: In step 3, the mass ratio of product B to cyclohexane is 1:10-11; the mass fraction of n-butyl lithium in the n-butyl lithium solution is 15%-20%, cyclohexane is selected as the solvent, and the mass ratio of n-butyl lithium to product B is 0.2-0.3:

1.

7. The preparation method according to claim 1, characterized in that: In step 3, the stirring speed is 200-300 rpm; the dropping speed of the n-butyl lithium solution is controlled at 0.5-2 mL / min; the reaction time is 4-6 h; anhydrous ethanol is used for washing; and the vacuum drying temperature is 40-60° C.

8. The preparation method according to claim 1, characterized in that: In step 4, the silicon source is mesoporous silica powder; the mass ratio of product C to silicon source is 1-3:1; ultrasound is applied for 30-60 min, and the ultrasonic power is 200-300 W; the stirring speed is 300-500 rpm; the reaction time is 2-4 h; and the vacuum drying temperature is 60-80 ° C.

9. The preparation method according to claim 1, characterized in that: In step 5, the vapor deposition reaction temperature is 600-800° C., the reaction pressure is 1-5 kPa, acetylene gas is introduced at a flow rate of 20-40 mL / min, and the reaction time is 2-4 h.

10. An anti-fading carbon composite modified negative electrode material for a power battery, characterized in that: The method is as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composite negative electrode material for lithium ion battery and preparation method of composite negative electrode material

    CN108054358A

  • Binder composition for lithium-ion secondary battery negative electrode, lithium-ion secondary battery negative electrode, and lithium-ion secondary battery

    US20240170674A1